INFLUENCE OF SQ3R MODEL AND FOR IMPROVING CAPABILITY AND THINKING CRITICAL MATHEMATICAL STUDY REVIEWED FROM STUDENT LEARNING MOTIVATION - Komara, Elis Siti; Wahyudin, Wahyudin; Sugandi, Asep Ikin ((JIML) JOURNAL OF INNOVATIVE MATHEMATICS LEARNING, 2018)
The problem raised in this research is due to lack of understanding and critical thinking of mathematics. In learning mathematics, learners often have difficulty in doing problems understanding and critical thinking mathematics. The learning process focuses on teachers instead of learning on the students. One of the learning models that teachers can do is the SQ3R model.This study aims to examine the picture of improving the ability of understanding and critical thinking of mathematics through learning model SQ3R and Direct Instruction in terms of learning motivation.This research is a quasi experimental research conducted at SMP IT Fithrah Insani in KBB. Two classes as a randomly selected sample. One class becomes experimental class gets SQ3R model treatment and one class becomes control class gets treated Direct Instruction model.The research stages begin with the making of instruments, the implementation of pretes, the implementation of learning, and postes. Done postes are given a motivation questionnaire that serves as a control variable. This pretest issue is shared by the researcher in the experimental and control classes to be performed by the students. After the problem is done, the students' work results are evaluated. After obtaining the pretest and posttest score in both classes, then calculated the gain to see the improvement result. Furthermore the gain data is processed, using SPSS 21 two-track anova test, to see the difference and interaction between the motivation level and the learning model. The result of data analysis shows that there is a difference of comprehension ability and critical mathematical thinking using SQ3R and Direct Instruction model but the level of motivation toward the learning model both on the ability of comprehension and the ability of thinking ability krits matematik. There is no interaction of motivation level and learning model.